علم الوقف والابتداء وعلاقتهما بتفسير القرآن الكريم - Mohammad Hikmat Shaker; Adnan Mohamed Yusoff; Abdoul Karim Toure (Universiti Sains Islam Malaysia, 2024)
This research aims to know the science of stopping and starting and their relationship to the interpretation of the Koran, as the stopping and starting are of the most important topics of the art of performance that the reader and the recipient must know. So it is the Holy art of knowing how to perform reading the Koran on stopping places that provided for readers to complete the meanings and starting placements which the Quran readers specify and not to be disrupted by the meanings. After reading, and research, found that the science of stopping and starting of the utmost importance and of great benefit. It is deemed aware of stopping and starting of the most important topics in Tajweed, which the reader of the Quran must have knowledge and observance of its reading of the Holy Qur'an forerunners of the first generation of interpreters that the reader of Quran must know the science of stopping and starting, and it has great importance and which have to seek a direct interpretation of the Koran, but to learn this art needs too many sciences," said Abu Bakr bin Mujahid: no one will exactly know when to stop only someone who is knowledgeable of interpretation, stories, and summarize some of them from other. As well as language jurisprudence, stopping and starting a strong knowledge of the interpretation because the interpretation science is looking for God intended meaning. As far as human ability takes it is comprehensive upon understanding the meaning which is the main aim of this research.